2014
DOI: 10.1111/petr.12415
|View full text |Cite
|
Sign up to set email alerts
|

Strain and strain rate imaging using speckle tracking in acute allograft rejection in children with heart transplantation

Abstract: Acute allograft rejection is a major cause of morbidity and mortality following heart transplantation. There is no reliable noninvasive test to diagnose rejection. We aimed to investigate the accuracy of strain by speckle tracking echocardiography in the detection of acute rejection. We identified acute rejection episodes in patients followed at a single transplant center. Data were collected at baseline, during rejection and two follow-up points. Peak systolic radial and circumferential strain at the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 30 publications
9
33
4
Order By: Relevance
“…2 In our present study, longitudinal strain and strain rate values of left ventricular lateral wall and of the middle segment of interventricular septum during rejection period were found to be lower than those during periods without rejection. However, statistically significant decreases were observed only in longitudinal strain and strain rate values of midseptum.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…2 In our present study, longitudinal strain and strain rate values of left ventricular lateral wall and of the middle segment of interventricular septum during rejection period were found to be lower than those during periods without rejection. However, statistically significant decreases were observed only in longitudinal strain and strain rate values of midseptum.…”
Section: Discussionmentioning
confidence: 74%
“…Hazim Alper Gursu, 1 Birgul Varan, 1 Elif Sade, 2 Ilkay Erdogan, 1 dilated cardiomyopathy in 3 patients, and restrictive cardiomyopathy in 3 patients (Table 1). All patients were symptomatic as New York Heart Association class I at time of biopsy.…”
Section: Evaluation Of Acute Rejection By Measuring Strain Andmentioning
confidence: 99%
“…The evaluation of rotational strain (torsion) has been related to alterations in exercise response in transplanted patients 15 . Significantly, an alteration of radial, longitudinal and circumferential strain has been observed in patients with episodes of rejection in relation to their baseline values, with recovery after the rejection episode resolves 6 . In our series, patients were asymptomatic at the time of the study and we only observed episodes of mild rejection (1R) in five out of nine patients in biopsy contemporary to echocardiography, with no episodes of moderate (2R) or severe rejection (3R), which also limits the detection of association with echocardiographic alterations.…”
Section: Discussionmentioning
confidence: 94%
“…However, since this is an invasive procedure with infrequent but potentially serious complications, it is necessary to find new noninvasive diagnostic tools in order to identify patients at risk of rejection and perform targeted confirmatory biopsies 4 . Different possible early rejection markers have been studied and the use of echocardiographic parameters of systolic function based on strain have been described [5][6][7] . The evaluation of myocardial strain allows quantifying the deformation of the myocardium in different axes, both in systole and diastole, in relation to time.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, there is no reliable noninvasive method to detect cardiac transplant rejection (CTR) aside from endomyocardial biopsy that remains as the “gold standard” invasive method for definitive diagnosis [54]. The advent of STE has been proposed as a possible alternative tool to monitor cardiac allograft function and define the best time to perform myocardial biopsies as well as coronary angiography [22].…”
Section: Clinical Applicationsmentioning
confidence: 99%